The Effectiveness of Electronic Deed Minutes Storage in Notarial Practice in the Digital Era - Situmorang, Saut Tua; Hafidz, Jawade (TABELLIUS: Journal of Law, 2025)
Abstract. This study aims to analyze: 1) Legal regulations in Indonesia that support the storage of electronic minutes of deeds in notarial practice. 2) The effectiveness of storing electronic minutes of deeds in notarial practice if implemented in the digital era. This type of research falls within the scope of normative legal research. The approach method in this study is a statute approach. The type of data in this study is secondary data, which consists of primary, secondary and tertiary legal materials. The data collection method was obtained through literature studies. The analysis in this study is prescriptive. The results of the study concluded: 1) Legal regulations in Indonesia have basically provided a sufficient basis to support the storage of electronic minutes of deeds in notarial practice, although they still require further strengthening and adjustment. The Notary Law (UUJN) has not explicitly regulated the technical aspects of storing minutes of deeds in electronic form, however, legal regulations in Indonesia have actually provided space for the digitalization of notarial archives through systematic interpretation of several provisions, such as Article 15 paragraph (3) of the UUJN and significant changes in Article 5 of the ITE Law which now no longer excludes notarial deeds from being recognized as valid electronic documents. 2) In the digital era, storing minutes of deeds electronically is considered very effective, especially from the aspects of efficiency, security, and ease of access. This effectiveness will be optimal if supported by regulatory updates, reliable digital infrastructure, increased digital literacy of notaries, and the acceptance of the legal culture of the community towards electronic systems.Keywords: Effectiveness; Electronic Deed Minutes; Notary.